2001
DOI: 10.21236/ada393374
|View full text |Cite
|
Sign up to set email alerts
|

Shock Response of Boron Carbide

Abstract: Boron carbide is of interest because of its potential application in protective systems both for personnel and structures. Therefore it is necessary to determine its mechanical response when subjected to impact loading. The present work was undertaken to determine tensile/spall strength of boron carbide under plane shock wave loading and to analyze all available shock compression data on boron carbide materials obtained from different sources. The principal conclusions are: (1) the tensile/spall strength of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 18 publications
3
36
1
Order By: Relevance
“…Therefore, B 4 C has been an important structural ceramic for the applications where both high strength and lightweight are required 6,7 . However, unlike other high performance ceramics, B 4 C displays an anomalous reduction in shear strength under pressures [8][9][10][11] . High-resolution electron microscopy of shock-loaded fragments revealed that the formation of nano-scale amorphous shear bands is responsible for the dramatic loss of shear strength at high pressures 12 .…”
mentioning
confidence: 86%
“…Therefore, B 4 C has been an important structural ceramic for the applications where both high strength and lightweight are required 6,7 . However, unlike other high performance ceramics, B 4 C displays an anomalous reduction in shear strength under pressures [8][9][10][11] . High-resolution electron microscopy of shock-loaded fragments revealed that the formation of nano-scale amorphous shear bands is responsible for the dramatic loss of shear strength at high pressures 12 .…”
mentioning
confidence: 86%
“…where 3 2520 kg/m o ρ = is the theoretical density of boron carbide [Dandekar, 2001]. These shock velocity versus particle velocity states, shown as the solid symbols in the right hand plot in Figure (10), provide sensible shock velocity versus particle velocity Hugoniot states within the hydrodynamic equation-of-state surface (the hydrodynamic Hugoniot) for boron carbide referenced from the initial theoretical density.…”
Section: Phase Transformation From Shock Hugoniot Datamentioning
confidence: 98%
“…In the range of 40 GPa shock pressure, containing a nice cluster of both 1900 kg/m 3 and 2400 kg/m 3 material Hugoniot points, temperatures of the lower initial density material subjected to Hugoniot shock compression are readily estimated. Based on a constant specific heat of 961.6 J/kg/K [Dandekar, 2001], an ambient average temperature rise due to shock heating is calculated to be about 2700 K. This level of temperature rise would approach the ambient melt temperature of boron carbide, which is also about 2700 K [Dandekar, 2001]. The specific heat can be expected to increase with temperature and therefore the calculated temperature rise is likely an overestimate.…”
Section: Phase Transformation From Shock Hugoniot Datamentioning
confidence: 99%
See 2 more Smart Citations